The Equine Gastrointestinal Microbiome: Impacts of Age and Obesity - Morrison, Philippa K.; Newbold, Charles J.; Jones, Eleanor; Worgan, Hilary J.; Grove-White, Dai H.; Dugdale, Alexandra H.; Barfoot, Clare; Harris, Patricia A.; Argo, Caroline McG (Frontiers in Microbiology, 2018)
Gastrointestinal microbial communities are increasingly being implicated in host susceptibilities to nutritional/metabolic diseases; such conditions are more prevalent in obese and/or older horses. This controlled study evaluated associations between host-phenotype and the fecal microbiome / metabolome. Thirty-five, Welsh Mountain pony mares were studied across 2 years (Controls, n = 6/year, 5-15 years, Body Condition Score (BCS) 4.5-6/9; Obese, n = 6/year, 5-15 years, BCS >7/9; Aged, n = 6 Year 1; n = 5 Year 2, ≥19 years old). Animals were individually fed the same hay to maintenance (2% body mass as daily dry matter intake) for 2 (aged / obese) or 4 (control), 4-week periods in a randomized study. Outset phenotype was determined (body fat%, markers of insulin sensitivity). Feces were sampled on the final 3 days of hay feeding-periods and communities determined using Next Generation Sequencing of amplified V1-V2 hypervariable regions of bacterial 16S rRNA. Copy numbers for fecal bacteria, protozoa and fungi were similar across groups, whilst bacterial diversity was increased in the obese group. Dominant bacterial phyla in all groups were Bacteroidetes>Firmicutes> Fibrobacter. Significant differences in the bacterial communities of feces were detected between host-phenotype groups. Relative to controls, abundances of Proteobacteria were increased for aged animals and Bacteroidetes, Firmicutes and Actinobacteria were increased for obese animals. Over 500 bacterial operational taxonomic units (OTUs) differed significantly between host-phenotype groups. No consistent pattern of changes in discriminant OTUs between groups were maintained across groups and between years. The core bacterial populations contained 21 OTUs, 6.7% of recovered sequences. Distance-based Redundancy Analyses separated fecal bacterial communities with respect to markers of obesity and insulin dysregulation, as opposed to age. Host-phenotype had no impact on the apparent digestibility of dietary GE or DM, fecal volatile fatty acid concentrations or the fecal metabolome (FT-IR). The current study demonstrates that host-phenotype has major effects on equine fecal microbial population structure. Changes were predominantly associated with the obese state, confirming an obesity-associated impact in the absence of nutritional differences. Clear biomarkers of animal-phenotype were not identified within either the fecal microbiome or metabolome, suggesting functional redundancy within the gut microbiome and/or metabolome.